The Political Economy of the African Continental Free Trade Area (AfCFTA): A Policy Analysis of the Prospects and Challenges - Soutar, Nicholas (Department of Political Studies, 2022)
This dissertation offers a policy analysis of the African Continental Free Trade Area (AfCFTA). The analysis aims to assess the prospects and challenges for implementation of the AfCFTA, and thereby to contribute to research on trade and regional integration in Africa and International Political Economy (IPE) theory testing. Throughout, emphasis is placed on the critical importance of both economic and political aspects of regional integration, which are often de-emphasised in conventional theoretical standpoints. The analysis highlights the need to avoid pursuing solely economic or political policy implementation and integration in order to achieve successful outcomes from the AfCFTA. Quintessential debates in regional theory are outlined. An analysis of the Eurocentric founding literature is undertaken, from which the origins of the false distinction between the state and the market in regional integration literature is identified. In the wake of the deficient explanatory capacity of European integration theories for African regionalism, alternate and more contemporary theoretical approaches are outlined, drawing from literature focussing on theories of new regionalism and the historical development of African regionalism. The slowing of regional integration globally, as well as the limited success of several aspects of Africa's overlapping Regional Economic Communities suggest that economic integration can only be sustained in environments where active political participation co-functions with successfully managed market integration. Thus, a political economy approach to the analysis and implementation of the AfCFTA is emphasised, in order to ensure both states and markets are incorporated into the regional integration literature. Research methods utilised include a review of regional integration literature, analysis of relevant macroeconomic data relating to international trade in Africa, a review of AfCFTA legal and policy documents, as well as situating the study within the wider theoretical body of regional integration literature and IPE. The analysis showed that despite critical challenges relating to implementation and coordination, the AfCFTA has significant potential benefits. It is concluded that a political economy approach to implementation would enhance the longterm prospects for regional integration in Africa and the AfCFTA specifically, by ensuring stakeholders in the political and economic spheres link their goals and methods of implementation to formulate long-term institutions for growth.